Bogotá: the collapse of a political machine (2007)
In Bogotá the 1991 reforms obstructed a market for votes. Clientelism lost its effectiveness; citizens developed a vote of opinion and the city showed an outstanding performance in the provision of public goods and social services. This story is illustrated with a novel panel data at the neighborhood voting precinct level from 1988 to 2003. An interesting episode exposes the changing class preferences of Bogotá citizens for each of its mayors. However, the main result is the structural break caused by the reforms. Prior to 1991, the areas with the most exposure to clientelism generated a greater percentage of votes for traditional parties and obtained a greater coverage of social services; since 1991, both relationships are no longer true. A political machine collapses.